2019
DOI: 10.1136/gutjnl-2019-319720
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in alcohol-related liver disease (ALD): summary of a Gut round table meeting

Abstract: Alcohol-related liver disease (ALD), which includes a range of disorders of different severity and is one of the most prevalent types of liver disease worldwide, has recently regained increased attention. Among other reasons, the realisation that any alcohol intake, regardless of type of beverage represents a health risk, and the new therapeutic strategies tested in recently published or undergoing clinical trials spur scientific interest in this area.In April 2019, Gut convened a round table panel of experts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 150 publications
(188 reference statements)
2
118
0
Order By: Relevance
“…Chronic alcohol use causes fatty liver and hepatitis 32 . We examined the potential influence of chronic stress on alcohol-induced liver injury.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic alcohol use causes fatty liver and hepatitis 32 . We examined the potential influence of chronic stress on alcohol-induced liver injury.…”
Section: Resultsmentioning
confidence: 99%
“…The early working model for ALD initiation demonstrated that portal circulation of the bacterial product lipopolysaccharide (LPS) from alcohol-induced gut leakage to liver-activated Kupffer cells (KCs) through LPS/Toll-like receptor (TLR) 4 signaling and subsequently produced inflammatory cytokines such as tumor necrosis factor alpha (TNF-α), leading to alcoholic liver injury. [1][2][3] In recent years, emerging evidence from preclinical and clinical studies has suggested that new immunological mechanisms are involved in all stages of ALD, including immune response initiation, inflammatory reactions, and completed/unresolved repair. 4 In the early stage, inducers/sensors, including alcoholic hepatocyte death, cause an immune response in the liver.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 5 Chronic liver injury leading to HCC development is mainly caused by HBV and HCV infections, long-lasting alcohol abuse and non-alcoholic fatty liver disease (NAFLD). 1 , 2 , 10 , 11 With the systematic implementation of HBV vaccination and the advent of effective anti-HCV therapies, it is likely that NAFLD will become the dominant cause of HCC in the coming years. 2 …”
Section: Introductionmentioning
confidence: 99%